"I'm scared that if I have the vaccine, it's going to make my lung condition worse, not better." COVID-19 vaccine acceptance in adults with underlying health conditions – A qualitative investigation. (December 2022) - Steffens, Maryke S.; Bullivant, Bianca; King, Catherine; Bolsewicz, Katarzyna
Abstract: Background: Sustained uptake of COVID-19 vaccines, including booster doses, will continue to be key to minimising morbidity and mortality caused by COVID-19. Because hesitancy can affect people's motivation to get vaccinated, understanding and addressing factors influencing acceptance is critical to achieving high uptake. This is especially the case for adults with underlying health conditions, who are at increased risk of severe illness from COVID-19. The aim of this study was to investigate barriers and facilitators of COVID-19 vaccine acceptance in adults with underlying health conditions during the initial rollout of COVID-19 vaccines in Australia. Methods: We conducted semi-structured, qualitative interviews with 15 adults with underlying health conditions in New South Wales (NSW) in April 2021, focusing on their previous vaccination experiences and feelings about COVID-19 vaccination. We categorised participants as accepting, hesitant or refusing. We analysed interviews thematically, informed by the World Health Organization (WHO) Behavioural and Social Drivers of Vaccination framework. Results: Most (12/15) participants were hesitant about COVID-19 vaccination. Barriers to COVID-19 vaccine acceptance included concerns about vaccine safety and effectiveness; heightened perceptions of risk regarding the vaccines; low perceptions of COVID-19 risk; and negative social influences. Facilitators included perceived benefits of vaccination and positive social influences. Conclusions: For some adults with underlying health conditions, perceptions of heightened vulnerability to COVID-19 vaccine side effects contributed to vaccine hesitancy during the initial rollout of COVID-19 vaccines. We recommend supporting GPs and specialists to proactively reach out and recommend COVID-19 vaccination to this population; encouraging chronic disease organisations to act as trusted advocates of COVID-19 vaccination; and actively communicating evolving knowledge about vaccine safety.